Polyphenol recovery from olive leaves and evaluation of the microbiological quality and antimicrobial potential of the extracts - Mirna Mrkonjić Fuka; Slaven Jurić; Luka Han; Martina Grdiša; Marko Vinceković; Irina Tanuwidjaja (Journal of Central European Agriculture)
During the production of olive fruit and olive oil, considerable quantities of leaves remain as by-products, which are a rich source of biologically active substances, especially polyphenols, and can therefore be used as a raw material for their extraction. Various methods are used for this purpose. One of them is ultrasound-assisted extraction (UAE), which has proven to be an effective and economically affordable method. The aim of this study was to compare the efficacy of ultrasound-assisted extraction (UAE) and conventional extraction (KE) in the extraction of total polyphenols from olive leaves using water as a solvent and to determine the antimicrobial activity of extracts as well as the microbiological purity of the olive leaves and the extracts obtained. In ultrasound-assisted extraction, the highest concentrations of polyphenolic compounds were extracted at an amplitude (A) of 100% in an extraction time of 6 min from 6 g leaf powder/L, and this method showed greater efficiency compared to the conventional extraction method. However, olive leaf extracts obtained showed no antimicrobial activity. Using a modified ultrasound-assisted extraction (MUAE) that includes lyophilization, an olive leaf extract with higher concentrations of total polyphenols was obtained, which showed an inhibitory effect on the bacteria Salmonella enterica subsp. enterica (DSM 14221), Escherichia coli (ATCC 25922) and Listeria innocua (ATCC 33090) at concentrations of 600 and 400 μg total polyphenols, while exhibiting an efficacy of up to 37.0% against conventional antibiotics in controlling infections caused by Gram-negative bacteria, i.e. up to 32.6% against antibiotics for controlling infections caused by Gram-positive bacteria. In addition, this study found that aerobic mesophilic and sporogenic bacteria, bacteria from the Enterobacteriaceae family and molds and yeasts make up the natural microbiota of the olive leaf. All extraction methods used had a bactericidal effect on species from the Enterobacteriaceae family and a fungicidal effect on molds and yeasts. However, aerobic mesophilic and sporogenic bacteria were found in all extracts, regardless of the extraction method used.